The Role of Competition in the Audit Market on Audit Quality and Audit Fees in the Iraqi Stock Exchange - Sahaeb Al-Haideri, Rasool Majid; Dastgir, Mohsen; Abdulhasan Jasim, Faez; Saedi , Rahman (Management Strategies and Engineering Sciences, 2025)
This study examines the impact of competition in the audit market on audit quality and audit fees within the Iraqi Stock Exchange. Audit market competition has been a subject of extensive debate, with conflicting perspectives on whether increased competition enhances or compromises audit quality. Some researchers argue that competition in the audit market lowers audit fees due to economies of scale and intense price competition among audit firms. Others contend that market concentration ensures auditor independence and improves audit quality. This study investigates these claims by analyzing financial data from 34 listed Iraqi companies between 2017 and 2023. Using multiple linear regression models, the study finds a significant inverse relationship between competition in the audit market and audit fees, confirming that increased competition leads to lower audit costs. However, results also indicate that greater competition negatively affects audit quality, suggesting that reduced auditor independence and fee pressure may lower audit rigor. These findings align with studies that highlight the potential risks of excessive market fragmentation in auditing. The study contributes to the literature by addressing gaps in empirical research on Iraq’s audit market, which has undergone significant structural changes following market liberalization. Policymakers and regulatory bodies, such as the Iraqi Board of Supreme Audit, should consider mechanisms to balance market competition with maintaining high audit quality. Encouraging consolidation among smaller audit firms and enhancing regulatory oversight may mitigate the adverse effects of excessive competition. Future research should explore the broader implications of audit market competition on corporate governance, financial reporting quality, and investor confidence in emerging markets.